Community Disadvantage, Prosocial Bonds, and Juvenile Reoffending: A Multilevel Mediation Analysis. (July 2017) - Intravia, Jonathan; Pelletier, Emily; Wolff, Kevin T.; Baglivio, Michael T.
Prior efforts suggest that adverse community contexts have the ability to impact juvenile recidivism. However, far less research has examined the indirect effects of community disadvantage on delinquent youth reoffending. As a result, it remains unclear whether several theoretically relevant mechanisms mediate the effects of disadvantage on continued delinquent behavior. Drawing from theoretical models of contextual effects, as well as social control theory, the present study examines whether prosocial bonds are salient mechanisms in the context–recidivism relationship. Using a sample of over 20, 000 juvenile offenders, our results indicate that both prosocial relationships and prosocial activities partially mediate the effect of community disadvantage on youth reoffending. Findings from the current study are discussed, along with policy implications and directions for future research in this area.